PROBABILITAS CAKUPAN INTERVAL KONFIDENSI DALAM REGRESI SETELAH DILAKUKAN UJI F AWAL (The coverage probabililty of confidence intervals in regression after a preliminary F test) - , Zainal Abidin,S.Pd. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Consider a linear regression model with regression parameter Î² = (Î²1, ...,Î²p) and independent normal errors. Suppose the parameter of interest is Î¸ = Î², where a is specified. Define the s-diminsional parameter vector Î² , where C and t are specified. Suppose that we carry out a preliminary F test of the noll hypothesis against the alternative hypothesis H1: . It is common statistical practice to then construck a confidence interval for Î¸ with nominal coverage 1 â , using the same data, based on the assumption that the selected model had been given to us a priori (as the true model). We call this the naive confidence interval for . This assumption is false and it may lead to this confidence interval haveing minimum coverage probability far below , making it completely inadequate